UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA TENTANG MENULIS PERMULAAN DENGAN MENGGUNAKAN MEDIA KARTU KATA PADA SISWA KELAS SDN BAJO - Hadijah M Saleh; Suhardi Abdullah (Jurnal Bilingual, 2020)
The research objectives consist of (1) Increasing prewriting activity through words card at 3rd grade of SDNegeri Bajo and (2) Increasing students prewriting activities through word cards. There were 22 students became the respondents of this reearch and this research used quantitative and qualitative approach with classroom action research (CAR). The result of this research showed that there was significant difference between 1st cycle and 2nd cycle showed up that there were positive and negatively reacting respond by the students. In using word cards media showed that students were more enjoyable in learning process. Based on the research result of learning foundout that 7,1 % average. It is proved that card words media could improved students competence in learning prewriting in cycle one with categorize suficiently. While in the second cycle became 19 students passed attend their evaluation or 19 students of 20 students, thus the percentage reach 95 %. Based on the second cycle of the research, the researcher assumed that the students prewriting competence through word cards increase atÂ  3rd grade of SDNegeri Bajo.